2021
DOI: 10.1186/s12876-021-01628-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node enlargement as the initial manifestation of rectal cancer

Abstract: Background Colorectal cancer is a very common malignant tumor worldwide. The clinical manifestations of advanced colorectal cancer include the changes in bowel habits, hematochezia, diarrhea, local abdominal pain and other symptoms. However, the colorectal cancer with an initial symptom of cervical lymph node enlargement is extremely rare. In this article, we report a case of rectal cancer presenting with cervical lymph nodes enlargement as the initial symptom. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…27,28 Therefore, we turned our focus to mLN NK cells because malignant CRC cells frequently migrate into mesenteric lymph nodes. [29][30][31] Metastatic CRC cells might constitute a cancer microenvironment in mLNs to alter NK cell activity. As a result, we revealed Sirt2 up-regulation in mLN NK cells especially exhausted NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Therefore, we turned our focus to mLN NK cells because malignant CRC cells frequently migrate into mesenteric lymph nodes. [29][30][31] Metastatic CRC cells might constitute a cancer microenvironment in mLNs to alter NK cell activity. As a result, we revealed Sirt2 up-regulation in mLN NK cells especially exhausted NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported the scarcity of NK cell infiltrates in the colon tissues of AOM/DSS‐treated mice 27,28 . Therefore, we turned our focus to mLN NK cells because malignant CRC cells frequently migrate into mesenteric lymph nodes 29–31 . Metastatic CRC cells might constitute a cancer microenvironment in mLNs to alter NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up, when provided, ranged from 4 months to 2 years with near complete resolution of disease to no evidence of recurrence. 66 67 68 69 70 Several other case reports describe the finding of a metachronous metastatic cervical node after a colorectal resection for adenocarcinoma. Again, the treatment varied significantly from surgery, chemotherapy, or radiotherapy alone or a combination of treatments.…”
Section: Distant Isolated Lymph Nodesmentioning
confidence: 99%
“…Cervical lymphadenopathies of unknown primary are a special challenge 1 . Most of them come from primary cancer of the head and neck, but sometimes the primary is in a remote site 2 . These cases pose a diagnostic challenge, especially when the cytology from the enlarged nodes does not clearly suggest a site of origin.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Most of them come from primary cancer of the head and neck, but sometimes the primary is in a remote site. 2 These cases pose a diagnostic challenge, especially when the cytology from the enlarged nodes does not clearly suggest a site of origin. In this report, we present a case of an asymptomatic man with cervical lymph node metastasis, suspected to be from a thyroidal primary site during an ultrasound screening program.…”
Section: Introductionmentioning
confidence: 99%